El cine tiene cuerpo de mujer - Hatfield, Elia (México, D.F. : Ediciones Eón, 2018)
Essays on discourse of female body and its representations in film. Is based particularly on analysis of late 20th-century films starring actress and politician Maria Rojo. Analyzes ways in which her characters subvert stereotypical constructions of body and portrays movement of avant-garde filmmakers to question male-dominated discourse of films made in 1950s-1970s.
Incluye referencias bibliográficas (páginas 161-173).
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Rojo, María, -- 1943-; Motion pictures, Mexican -- History -- 20th century; Women in motion pictures; Human body in motion pictures; Women motion picture producers and directors; Motion picture actors and actresses; Películas mexicanas -- Historia -- Siglo XX; Mujeres en películas.; Cuerpo humano en imágenes en movimiento; Mujeres productoras y directoras de cine; Actores y actrices cinematográficos.; Libros electrónicos.